IMPLEMENTASI SISTEM PENGENDALIAN INTERN TERHADAP PIUTANG PADA UNIVERSITAS DJUANDA BOGOR - Hambani, Susy (JURNAL AKUNIDA, 2015)
The implementation of Internal Control System receivable account at the Djuanda University more selling their services on credit and receivables has a relatively large value of the total assets owned university often resulting in problems such as a delay in the receipt of payment, less careful in bookkeeping. The object of this research is a Private University in Bogor. The design research used explanatory method, the data collection techniques used Study Library and Study pitch. Analyzing data with descriptive method, and the method of data analysis with comparative descriptive techniques. The results showed Receivable Accounting Systems Implementation of SPP in general have been carried out properly. This is demonstrated by the implementation of elements implementation of Internal Control System, which is the application of internal element check that the accuracy of data and information can be achieved, but there are still weaknesses in the internal control system of the other.Keywords: Internal Control System, Accounts Receivable, Djuanda University